Morphological evolution and visible light driven degradation of tetracycline by Bi3.84W0.16O6.24 nanostructures. Issue 82 (5th September 2015) - Li, Xinying; Wang, Liping; Shi, Weidong; Song, Chengjie; Xu, Dongbo; Liu, Jingjing
<x xml:space="preserve">Abstract</x> In this work, two morphologies of Bi3.84W0.16O6.24 nanostructures, namely the nanobelt (T2) and nanooctahedral structure (T15), were synthesized via a simple, microwave-assisted method.